Síntese e caracterização de copolímeros do tipo ABA para encapsulação de hemoglobina bovina - Felipe F. Lima; Cristina T. Andrade (Química Nova, 2012)
The use of biopolymers for the development of oxygen carriers has been extensively investigated. In this work, three different ABA triblock copolymers were synthesized and used to encapsulate purified bovine hemoglobin, using a double emulsion technique. The effect of polymer composition, homogenization velocity, and addition of a surfactant, on the protein entrapment was evaluated. These copolymers, which have a hydrophilic block, achieved higher values of encapsulation efficiency than the corresponding homopolymers. The increase in homogenization strength also promoted an increase in encapsulation efficiency. Capsules formation occurred even in the absence of PVA.